MEMBANGKITKAN SEMANGAT PEDULI LINGKUNGAN MELALUI PENGOLAHAN LIMBAH BAHAN BERBAHAYA DAN BERACUN (B3) RUMAH TANGGA DI RANCAEKEK - Hasan Sidik; Neneng Konety; Savitri Aditiany (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2018)
This research tries to discuss the processing of Hazardous and Poisonous Substances Waste (B3) in the closest community that is namely household B3 waste. Rancaekek is a sub-district with a large number of industries, for a long time the people of the region felt the negative impact of industrial waste on their environment but did not find an effective solution until now. Therefore this research was conducted with the aim of trying to provide socialization and education regarding the management of B3 waste to the people in the Rancaekek sub-district by practicing at the household level. This is an effort to reduce pollution of B3 waste in this sub-district. The research method used is qualitative and the technique of data collection was carried out by interviewing the people scattered in the Rancaekek area, namely Rancaekek Wetan Village, Rancaekek Kulon and Linggar Village. From this research, the community now understands the basic knowledge of B3 waste which not only comes from industry but also in daily life can not be separated from products containing B3 waste. Through this socialization, the community gained more knowledge about the types of B3 waste explained by the Government Regulation No. 85 of 1999. Then also an explanation of the management of household B3 waste in order to reduce the impact of household B3 waste by referring to the rules of Government Regulation No.101 of 2014. The stages of B3 waste management consist of: a) Temporary Storage of B3 Waste; b) Transport of B3 Waste; and c) B3 Waste Storage and Collection.